The effect of demand response and wind generation on electricity investment and operation - Sheila Nolan; Mel Devine; Muireann Á. Lynch; Mark O'Malley (The Economic and Social Research Institute (ESRI), 2017)
We present a novel method of determining the contribution of load-shifting Demand Response (DR) to energy and reserve markets. We model DR in an Mixed Complementarity Problem (MCP) framework with high levels of wind penetration. Investment, exit and operational decisions are optimised simultaneously. We examine the potential for DR to participate in both energy and reserve markets. DR participation in the energy market reduces costs and prices but the impact of DR participation in reserve markets is limited. DR and wind generation are strongly complementary, due to the ability of DR to mitigate against the variability of wind generation, with the highest impacts of DR seen at high levels of wind penetration. DR participation in the energy market gives rise to lower equilibrium levels of investment in conventional generation and induces a Pareto improvement versus a market with no DR participation. The total impact of DR is highly dependent on specific system characteristics.
Keywords: Q4; D43; D47; L13; C61; 330; Demand Response; Load shifting; Electricity markets; Mixed complementarity problem; Reserve